Parametric analyses for a single layered aerogel-based coating using thermal spray for aerospace applications - Bheekhun, Muhammad Ibrahim-Nadiir (2017)
Since its discovery in 1931, silica aerogel has been incorporated mainly as flexible blankets for thermal insulation applications in the aerospace arena. However, despite being considered as the world’s best thermal insulator it cannot be often applied due to weight and space constraints. This research proposes an innovative route to achieve a single-layered micro-thick thermally sprayed coating and its targeted objectives are ranking the available aerogel powders for plasma spraying based on their evaluated physical properties, formulating and analysing the parameters of an optimised spray-dried aerogel-based powder for atmospheric plasma spraying (APS) and deducing the spraying conditions for surface adhesion of a single layered aerogel-based plasma sprayed coating. Firstly, the different silica aerogel powders were characterised to value their physical properties and their suitability for atmospheric plasma spraying (APS) and suspension plasma spraying (SPS) were ranked. Secondly, slurries of ceramics composed of aerogel and yttria stabilized zirconia were formulated followed by spray-drying, subjected to the Taguchi Design to obtain an optimised sprayable granulated powder. Technical installations and plasma spraying design parameters such as nozzle diameter, electric power, plasma gas flow rate, carrier gas flow rate, concentration of aerogel and dispersant were varied methodically until it could be deduced whether an adhering coating could be achieved or not using the selected aerogels. Characterisation of the coatings using scanning electron microscopy was then performed. Out of six aerogel powders, only GEATM 0.125 and Enova® IC3100 were opted for plasma spraying. After statistical analysis, the optimised powder YSZ-aerogel spray-dried powder was characterised and had a median particle size of 28.932±0.726 μm, volume fraction of 64.450±0.535 vol.% and uniformity of 0.475±0.002μm. An amelioration in the morphology of the aerogel particles from irregular shapes to spherical and donut-like granulated YSZ-aerogel particles was observed. However, due to low yield of only 10%, the granulated powder could not be opted for subsequent APS. A coating was achieved using APS of as-received GEATM 0.125 under spraying conditions of a nozzle diameter of 4 mm powered at 25 kW with a plasma gas rate of 45+5 slpm and carrier gas flow rate of 8.1 slpm. The coating had a bimodal microstructure with a thickness ranging from 77.9 μm to 132.0 μm. SPS was not successful neither with GEATM 0.125 nor Enova® IC3100. Blockage due to agglomeration prevented the injection of GEATM 0.125 into the plasma. Enova® IC3100 could nevertheless be propelled onto the glass substrates but no melting of particles occurred which was thought because of insufficient power supplied by the plasma gun. Conclusively, not all available aerogel powders can be used for thermal spray applications. Tailoring aerogel particles using spray-drying to make them sprayable using APS is not necessary as it had been proven that GEATM 0.125 can be deposited in its as-received powder form using APS. SPS seems to be promising using Enova® IC3100 and a suspension-plasma sprayed coating can be achieved using a plasma gun with an electric power higher than 40 kW.